OPTIMIZATION OF CONSTRUCTIVE PARAMETERS OF SOLID PLANTING COULTER - Павельчук, Ю. Ф.; Гевко, Б. М.; Рудь, А. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The issue of reducing energy costs of machine and tractor aggregate for grain crops has been established and the advantages of its solution are shown. The study presents an overview of literary sources on the interaction between a wedge cutting unit and different types of soils during their surface cultivation. A graphical analysis of the power interaction between pointed coulter of the grain opener and soil is made and all the components of the power interaction are described. The mathematical model of the total resistance force to the propeller motor with the doubled last plug that considers the presence of two symmetrically located blades at the coulter is given. The influence of the entering angle of the coulter on the size of the traction effort has been investigated. The author suggests creating a coulter construction with minimal traction effort. The optimum value of the entering angle of the coulter is set in the range of 40 - 60 degrees that serves as self-cleaning and gives enough space inside the paw of the coulter to form the channels for passing the seed material. The author argues that application of a semi-circular paw with an angle of less than 50 degrees makes it possible, at the expense of a relatively longitudinal size, to easily place the seed tube inside the paw, to reduce its movement forces in the soil and to promote the self-cleaning of the paw from sticking soil